Product Recommendation System using SVD and Machine Learning techniques - En, Joanne Lim Jo; Li, Chong Kae; Yen, Davina Lim Zhe; Jian, Chan Vern; Salam, Zailan Arabee Bin Abdul (Journal of Applied Technology and Innovation, 2024)
Recommendation system is commonly used in many areas. Machine learning is the new trend in the field of analysis data. In this study, recommendation system is also applied to machine learning; the AI methods implemented in this recommendation system are Collaborative Filtering and Content-based Filtering. The demonstration of the result is present in this study too. The articles reference a few papers: Crop Plantation Recommendation using Feature, Product Based Recommendation System Using Machine Learning Techniques, Product recommendation based on shared customer’s behaviour, recommender systems enhancement using deep reinforcement learning.